Precise Estimates for the Time Complexity of Implementing Algorithms of Set-Theoretic Operations in Table Algebras - Red’ko, V. N.; Buy, D. B.; Kanarskaya, I. S.; Senchenko, A. S. (Cybernetics and systems analysis, 2017)
Algorithms implementing intersection, union, and difference in table algebras are investigated. Modifications of the most widespread algorithms reducing the amount of computations are proposed. Based on the complexities evaluated in the worst case and on the average for the modified algorithms, the fastest algorithm is found for each operation. A program that experimentally confirms theoretical estimates is developed.